Sistem Inferensi Fuzzy untuk prediksi Sindrom Metabolik bagi penyandang Penyakit Ginjal Kronik - Muhammad Zainudin Al Amin; Sri Kusumadewi; Linda Rosita (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2021)
Patients with Chronic Kidney Disease (CKD) are increasing every year. One of the risk factors is due to metabolic syndrome because components in the metabolic syndrome are the cause of risk factors for CKD. The purpose of this study is to build a fuzzy inference system to predict metabolic syndrome for people with CKD. The method in this research is through literature study in building fuzzy rules and forming a fuzzy inference system. The variables used are body mass index, blood pressure, triglycerides, HDL and fasting blood sugar. System testing was carried out on eight hemodialysis patient data. The results of the system test are able to provide information related to the percentage of metabolic syndrome risk levels in 7 patients with chronic kidney disease.